Synthesis and Catalytic and Biological Activities of Silver and Copper Nanoparticles Using Cassia occidentalis - Manjul Gondwal; Geeta Joshi nee Pant (International Journal of Biomaterials)
An ecofriendly and green method for the synthesis of silver and copper nanoparticles has developed using aqueous leaves extract of Cassia occidentalis. The formation of AgNPs and CuNPs was monitored by measuring the UV-Vis spectra. The morphology and crystalline phase of the metal nanoparticles were determined using transmission electron microscopy (TEM) and scanning electron microscopy (SEM) with X-ray energy dispersive spectrophotometer (EDX) and X-ray diffraction (XRD). The synthesized metal nanoparticles were generally found to be spherical and oval in shape. The AgNPs and CuNPs showed highly potent antibacterial activity against Escherichia coli and Salmonella typhi bacteria, respectively. The CuNPs showed higher radical scavenging activity than AgNPs. The AgNPs showed lower haemolysis (1.7%) exhibiting lesser toxicity as compared to CuNPs. The CuNPs have better catalytic ability for the reduction of 4-nitrophenol and 2-nitrophenol as compared to AgNPs.